2009
DOI: 10.2528/pierl09051204
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Pattern Retrieval in Non-Anechoic Chambers Using the Matrix Pencil Algorithm

Abstract: In this paper, the Matrix-Pencil method is used to retrieve the radiation pattern of several antennas measured in different semianechoic scenarios using low directive probes, where the existence of reflected contributions can severely disturb the measurement. Starting from data measured in the frequency domain, this method allows the direct path to be identified and the radiation pattern of the antenna to be retrieved with good accuracy in all the cases under study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…A proper model of RF microwave absorber must be developed based on various parameters such as the absorber reflection loss, the magnitude and phase, for various angles of incidence, and for parallel and perpendicular polarizations [4,12,20,21]. The reflection loss, R, can be expressed as the absorbing performance of the material and is a function of the complex permittivity, permeability of the material, and the frequency of the electromagnetic wave [22].…”
Section: Introductionmentioning
confidence: 99%
“…A proper model of RF microwave absorber must be developed based on various parameters such as the absorber reflection loss, the magnitude and phase, for various angles of incidence, and for parallel and perpendicular polarizations [4,12,20,21]. The reflection loss, R, can be expressed as the absorbing performance of the material and is a function of the complex permittivity, permeability of the material, and the frequency of the electromagnetic wave [22].…”
Section: Introductionmentioning
confidence: 99%
“…We can either use (11) or (14) to model the measurement scenario in the presence of echoes. Which of the two equations will be more useful will depend on the problem at hand.…”
Section: Reconstruction For Measurements With Echoesmentioning
confidence: 99%
“…Sometimes, it is possible to model the echo influences directly, if for example exact knowledge of geometry and material composition of a scattering object is given and the echo influence can directly be included in the linear model (9) [36]. More often, however, neither the echolocation nor the echo response for incident fields is known with sufficient accuracy for the echo objects, such that a direct echo modelling according to (11) or (14) is not feasible.…”
Section: Reconstruction For Measurements With Echoesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many shapes of microwave absorber that have been used in research, including pyramids, wedges, convoluted shapes, metamaterial bases, and oblique [34][35][36][37][38][39][40][41][42][43][44][45]. The recent research by Nornikman et al showed that rice husks can be an alternative natural material for designing a pyramidal microwave absorber.…”
Section: Development Of Pyramidal Microwave Absorbermentioning
confidence: 99%